EFEKTIVITAS METODE INTERAKTIF PADA PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - Zalukhu, Anto; Yulia, Tantri; Manik, Disetra Fiser (JOURNAL of THEOLOGICAL STUDENTS, 2024)
The hypothesis in this study is the level of effectiveness of the interactive method in learning Christian religious education in grade 2 at SMP Negeri 4 Alasa Nias Utara. Based on the hypothesis testing conducted, the researchers found that the level of effectiveness of the interactive method in learning Christian religious education in grade 2 of SMP Negeri 4 Alasa Nias Utara for the 2021/2022 academic year is in the good category, namely 67.9%.